Improvement of Pain Management by Nefopam in a Rat Adjuvant-Induced Arthritis Model - Dalix, Elisa; Maalouf, Mathieu; Linossier, Marie-Thérèse; Vanden-Bossche, Arnaud; Peyroche, Sylvie; Marotte, Hubert (Frontiers in Veterinary Science, 2022)
Introduction The adjuvant-induced arthritis (AIA) model is widely used in research to investigate arthritis pathogenesis. Hind paw inflammation is the main outcome in this model with high loss of mobility function partly related to pain. However, analgesics such as non-steroidal anti-inflammatory drugs or opioid drugs interfere with the inflammation process related to arthritis, thus reducing their beneficial use in this model. Therefore, we investigated the effect of nefopam on arthritis development in order to improve pain management in the AIA model. Methods Female Lewis rats were randomly divided into two groups, and each group received an injection of Mycobacterium butyricum on defining day (D) 0. At D6, rats (n = 10) received nefopam (intraperitoneally or orally) or NaCl 0.9% IP or 1% sucrose in water (n = 5 for each). Rats were monitored with the arthritic index (AI) and ankle circumference. Pain was assessed by scoring based on behavioral indicators. Histology, RT-qPCR, and microcomputed tomography were performed. Results The clinical parameter AI and ankle circumference were not different in both groups at various time points. However, pain score was significantly lower in the nefopam group at the early stage of the disease. At a later stage of the disease, inflammation was mildly lower whereas bone erosion and bone loss parameters increased in the nefopam group. Conclusion Nefopam provided a slight reduction in the level of pain at the arthritis onset without reducing arthritis severity and bone loss in the rat AIA model. However, it should be administrated orally for a shorter period to avoid inflammation reduction in the long run.